High-utility action rules mining - Hrudková, Kateřina (2022)
High utility action rules mining is a data mining task, that aims to generate such rules, that would provide the user with the information of which actions might be the most profitable. To the author’s best knowledge, no open-source solution for high utility action rules mining has not been proposed to date. The aim of this paper is to present reader with brief background of the key topics (frequent itemset mining, action rules mining, high utility itemset mining) related to the high utility action rules mining and ActionRules package and to implement a practical solution in Python, to the existing ActionRules package framework, that would enable high utility action rules mining. The chapters on frequent itemset mining, action rules mining, high utility itemset mining and part of the last chapter on high action rules mining were processed by the method of narrative literature search. Through the method of analysis, the workflow of ActionRules package was observed and on the insights of the analysis the aimed high utility action rules mining solution has been implemented to the existing ActionRules framework.